From telomere to telomere: The transcriptional and epigenetic state of human repeat elements - Hoyt, Savannah J; Storer, Jessica M; Hartley, Gabrielle A; Grady, Patrick G S; Gershman, Ariel; de Lima, Leonardo G; Limouse, Charles; Halabian, Reza; Wojenski, Luke; Rodriguez, Matias; Altemose, Nicolas; Rhie, Arang; et al. (Science (American Association for the Advancement of Science), 2022)
Mobile elements and repetitive genomic regions are sources of lineage-specific genomic innovation and uniquely fingerprint individual genomes. Comprehensive analyses of such repeat elements, including those found in more complex regions of the genome, require a complete, linear genome assembly. We present a de novo repeat discovery and annotation of the T2T-CHM13 human reference genome. We identified previously unknown satellite arrays, expanded the catalog of variants and families for repeats and mobile elements, characterized classes of complex composite repeats, and located retroelement transduction events. We detected nascent transcription and delineated CpG methylation profiles to define the structure of transcriptionally active retroelements in humans, including those in centromeres. These data expand our insight into the diversity, distribution, and evolution of repetitive regions that have shaped the human genome.